Microstructural elucidation of self-emulsifying system: effect of chemical structure - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2012)
Self-emulsifying systems (SES) emulsify spontaneously to produce fine oil-in-water emulsion when introduced into aqueous phase. The self-emulsification process plays an important role during formation of emulsion. The objective of current work was to understand and explore the inner structuration of SES through controlled hydration and further to study the influence of additive on the same which ultimately governs performance of final formulation in terms of droplet size. Droplet size of final formulations containing structural analogues of ibuprofen was determined. Microstructural properties of intermediate hydrated regimes of SES were investigated using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. The current work established inverse relationship between droplet size of the formulations containing structural analogues of ibuprofen and their Log P values. Microstructural analysis of intermediate hydrated regimes of the prepared samples showed formation of local lamellar structure. Structural analogues of ibuprofen significantly altered microstructure of lamellae which was well correlated with the droplet size of final formulations. In vitro drug release study showed increase in dissolution rate of lipophillic drugs when formulated as SES. The current work emphasizes the fact that tailor-made formulations can be prepared by controlling the properties of intermediate regimes.
Keywords: emulsion; flurbiprofen; ibuprofen; ketoprofen; lamellar structure; self-emulsifying system; structural analogues

Probing influence of mesophasic transformation on performance of self-emulsifying system: effect of ion - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Molecular Pharmaceutics, 2012)
Self-emulsifying systems are mixtures of oils and surfactants, ideally isotropic, sometimes including cosolvents, which emulsify under conditions of gentle agitation, similar to those which would be encountered in the gastrointestinal tract. The process of self-emulsification has remained the center of attraction for most researchers. Controlled hydration of self-emulsifying systems shows formation of an intermediate gel phase which upon rupture forms an emulsion. Current work was undertaken to understand and explore the microstructural properties of intermediate gel phase which are believed to influence the performance (droplet size) of the final formulation. The effect of additives on microstructural properties of intermediate gel phase has also been investigated. Microstructural elucidation of hydrated samples of intermediate regimes was done by using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. Samples from intermediate regimes showed formation of local lamellar structure which swelled with hydration. In the present work, the effect of addition of salt form of naproxen (sodium and potassium) and naproxen (base) on microstructural properties of intermediate regimes was investigated. Systems containing naproxen salts formed larger droplets whereas naproxen base formed smaller ones. Microstructural properties of intermediate lamellar structures were well correlated with performance of the final formulation. The current studies indicate that by controlling the properties of intermediate regimes optimized formulations with desired performance can be tailor-made.
Keywords: emulsion; lamellar structure; liquid crystal; Microstructure; Naproxen; self-emulsifying system

Mapping ion-induced mesophasic transformation in lyotropic in situ gelling system and its correlation with pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2013)
To investigate influence of ion induced mesophasic transformation on pharmaceutical performance of in situ gelling system consisting of glyceryl monooleate. The prepared system showed mesophasic transformation during its conversion from sol to gel upon controlled hydration. The process of mesophasic transformation was studied by SAXS, DSC, rheology and plane polarized light microscopy. Further the influence of additives i.e. naproxen salts (sodium and potassium) and naproxen (base) on the process of mesophasic transformation was also elucidated. It was observed that addition of salt form of naproxen transformed W/O emulsions into cubic mesophase whereas addition of base form of naproxen formed reverse hexagonal (H-II) phase upon controlled hydration. The cubic mesophase formed by naproxen salts retarded the drug release for initial 3 h whereas H-II phase showed sustained drug release characteristics for naproxen base following Higuchi drug release kinetics. The current work suggests that formulations with tailor made pharmaceutical performance can be developed by selecting proper additives in the system so as to obtain the desired mesophase `on demand' thereby controlling drug release characteristics.
Keywords: cubic phase; hexagonal phase; liquid crystal; mesophasic transformation; sustained drug release

Exploring microstructural changes in structural analogues of ibuprofen-hosted in situ gelling system and its influence on pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (AAPS Pharmscitech, 2015)
The present work explores inner structuration of in situ gelling system consisting of glyceryl monooleate (GMO) and oleic acid (OA). The system under study involves investigation of microstructural changes which are believed to govern the pharmaceutical performance of final formulation. The changes which are often termed mesophasic transformation were analysed by small angle Xray scattering (SAXS), differential scanning calorimetry (DSC), rheology and plane polarised light (PPL) microscopy. The current work revealed transformation of blank system from W/O emulsion to reverse hexagonal structure upon addition of structural analogues of ibuprofen. Such transformations are believed to occur due to increased hydrophobic volume within system as probed by SAXS analysis. The findings of SAXS studies were well supported by DSC, rheology and PPL microscopy. The study established inverse relationship between log P value of structural analogues of ibuprofen and the degree of binding of water molecules to surfactant chains. Such relationship had pronounced effect on sol-gel transformation process. The prepared in situ gelling system showed sustained drug release which followed Higuchi model.
Keywords: flurbiprofen; hexagonal phase; ibuprofen; ketoprofen; liquid crystal; sustained drug release

Tracing the architecture of caffeic acid phenethyl ester cocrystals: studies on crystal structure, solubility, and bioavailability implications - Ketkar, Sameer; Pagire, Sudhir K.; Goud, N. Rajesh; Mahadik, Kakasaheb R.; Nangia, Ashwini; Paradkar, Anant (Crystal Growth & Design, 2016)
Caffeic acid phenethyl ester (CAPE) is a polyphenolic active compound present in popular apiproduct, "propolis", obtained from beehives, Though it has broad therapeutic capability, the bioavailability of CAPE is limited due to poor solubility. In this study, we report novel cocrystals of CAPE engineered using coformers such as caffeine (CAP), isonicotinamide (INIC), and nicotinamide (NIC) with enhanced solubility and bioavailability of CAPE. The cocrystals were prepared by microwave-assisted cocrystallization and characterized using PXRD, DSC, and Raman spectroscopy. PXRD and DSC confirm the successful formation and phase purity of CAPE-CAF, CAPE-INIC, and CAPE-NIC cocrystals. Raman spectra of CAPE cocrystals complement these results in confirming the formation of novel crystalline phases. CAPE-NIC cocrystal was further subjected X-ray crystallography to understand its molecular arrangement and hydrogen bonding in the crystal structure. The CAPE-NIC cocrystal structure is found to be stabilized by a rare 1,2-benzenediol-amide heterosynthon. Cocrystallization of CAPE with NIC improved its aqueous solubility and pharmacokinetic profile, thereby demonstrating a 2.76-fold escalation in bioavailability.

Rivaroxaban eutectics with improved solubility, dissolution rates, bioavailability and stability - Shaligram, Parth S.; George, Christy P.; Sharma, Himanshu; Mahadik, Kakasaheb R.; Patil, Sharvil; Vanka, Kumar; Arulmozhi, S.; Gonnade, Rajesh G. (Crystengcomm, 2023)
Rivaroxaban (RXB) is a direct factor Xa inhibitor used for the treatment of deep vein thrombosis (DVT, a blood clot in the leg) and pulmonary embolism (PE, a blood clot in the lung) and to prevent blood clots in atrial fibrillation following hip or knee surgery. However, RXB suffers from poor solubility that hinders its broader application. Although its cocrystals are reported for solubility enhancement, the methodology used to prepare multi-component crystals is complex. Also, it uses hazardous solvents to develop cocrystals. We have prepared eutectics of RXB with caffeic acid (CAA), coumaric acid (CA), fumaric acid (FA), succinic acid (SA), mandelic acid (MA) and trimesic acid (TA) and analyzed them using hot stage microscopy (HSM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and fourier transform infrared spectroscopy (FTIR) techniques. The saturation solubility and dissolution rate profiles were also obtained to investigate the effect of eutectics on these parameters. Amongst all the coformers tested, coformers CAA, CA, and FA showed significant enhancement in the solubility of RXB. The powder dissolution rate of the eutectics showed considerable enhancement compared to that of RXB. In vivo pharmacokinetic study was carried out for RXB-CAA, RXB-CA and RXB-FA in rats and compared with RXB, which showed 1.5 and 1.4 times enhancement in relative bioavailability for RXB-CAA and RXB-CA, respectively. Stability studies were carried out as per ICH guidelines for all the eutectics, which revealed excellent stability over six months under accelerated (40 degrees C and 75%) conditions and twelve months under long-term (30 degrees C and 60% RH) conditions. The DFT studies carried out using the B3LYP/TZVP level of theory revealed higher Gibbs free interaction energy (Delta G(int)) for homosynthons (drugMIDLINE HORIZONTAL ELLIPSISdrug and coformerMIDLINE HORIZONTAL ELLIPSIScoformer) than heterosynthons (drugMIDLINE HORIZONTAL ELLIPSIScoformer).